Improvement of change glue schedule down time at lid attachment process for semiconductor devices - Abd Rahman, Rozeana (UTeM, 2017)
This research report presents the work done on the improvement of change glue schedule down time at lid attachment process for semiconductor devices. Lid attachment is the end of line process for Plastic Dual Small Outline Flat (PDSOF) package which is one of the semiconductor devices. The process is started with pick and places the lid onto the package, then proceeds to glue dispensing with dosage on four corners of the lids to completely seal the package by using capillary effect. There is a change of glue activity in this process which is counted under schedule down time. Based on the Overall Equipment Effectiveness (OEE), it was found that the change of glue activity give impact on the machine performance. The increasing of change glue time will result in the production did not achieve the target productivity. In this research, the hidden losses were defined on the equipment setup which is changed of glue in the lid attachment process. There is plan to increase the amount of glue lid attach to reduce the schedule down time in order to improve overall equipment effectiveness toward achieving good productivity. The study for glue pot life is required since increasing the amount of glue will extend the glue pot life and it is suspected will increase the glue viscosity. In general, all the project objective are managed to be achieved using the developed research methodology. For future work, this research should be enhance further to achieve better result and to make use of the increasing glue amount and pot life extended time enhancement in other perspective field and also to carry out further study to improve on the whitish on lid surface.